Original Reaction Sequence of Pb(Yb1/2Nb1/2)O3-PbTiO3: Consequences on Dielectric Properties and Chemical Order - Charlotte Cochard; Fabienne Karolak; Christine Bogicevic; Orland Guedes; Pierre-Eymeric Janolin (Advances in Materials Science and Engineering, 2015)
The solid solution [Pb(Yb1/2Nb1/2)O3]1−x-[PbTiO3]x was synthesized with x≤60%, using several high-temperature techniques as well as room-temperature mechanosynthesis. The high-temperature synthesis reveals a reaction path involving the synthesis first of the end-members before the solid solution. The density and dielectric constant measured on the ceramics prepared from these powders indicate the crucial role of the synthesis technique in the subsequent properties. Mechanosynthesis results in ceramics with higher density and dielectric constant. Identical optimized sintering conditions were then applied to all investigated compositions and the resulting dielectric properties and chemical orders were compared. All polar orders (antiferroelectricity, ferroelectricity, and relaxor behavior) were evidenced. The 1 : 1 chemical order on the B-site of Pb(Yb1/2Nb1/2)O3 results in the formation of a double perovskite Pb2YbNbO6, and the superstructures in the X-ray diagrams signing the existence of this order persist up to 30% PbTiO3. The underlying mechanism for substitution of Yb or Nb by Ti is presented.